2020
DOI: 10.1155/2020/9259852
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Suppressed Esophageal Squamous Carcinoma Growth by Blocking EGFR Activation and Inducing Cell Cycle Arrest

Abstract: Isoliquiritigenin (ILQ) is a natural product isolated from licorice root which has served as traditional Chinese medicine for a long time. Recently, the antitumor effects of ILQ have been widely studied in various cancers, but the role and related mechanisms of ILQ in esophageal squamous carcinoma cells (ESCC) are still poorly understood. In our studies, ILQ showed profound antitumor activities in ESCC cells. In vitro, ILQ substantially inhibited cell proliferation and anchorage-independent growth in a panel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…Intracellular signaling plays predominant roles in regulating tumor malignant features 37 . In ESCC, EGF‐induced activation of PI3K/AKT and ERK1/2 pathways was well elucidated 38,39 . Our results are consistent with the findings of previous studies, demonstrating that these intercellular signaling pathways were under the regulation of HOXA7 both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Intracellular signaling plays predominant roles in regulating tumor malignant features 37 . In ESCC, EGF‐induced activation of PI3K/AKT and ERK1/2 pathways was well elucidated 38,39 . Our results are consistent with the findings of previous studies, demonstrating that these intercellular signaling pathways were under the regulation of HOXA7 both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Its isoflavane glabridin reported downregulation of the increased myofibroblast activities caused by arecoline‐ induction and a decrease in the levels of α‐SMA, type I collagen, and TGF‐β in fBMFs (Lee et al, 2018). On the other hand, Ye et al (2020) confirmed the anti‐cancer property of isoliquiritigenin against esophageal squamous carcinoma cells (ESCC) by decreased cell proliferation as well as inhibition of EGFR activation and its downstream Akt and ERK1/2 signaling pathway. A Chinese herb Salvia miltiorrhiza famous by the name “Danshen” was also described by several authors for its anti‐fibrotic potential in addition to known antioxidant and anti‐inflammatory activity.…”
Section: Plant Leads For Oral Submucous Fibrosismentioning
confidence: 99%
“…Ye et al reported the anti-metastatic effects of isoliquiritigenin (ISL) as a novel remedy to treat esophageal cancer [ 34 ]. For 72 h, 20 μM of ISL resulted in the lowest survival number of cancer cell colonies in various esophageal squamous cancer cell lines by downregulating AP-1 and cyclin D1.…”
Section: Anti-esophageal Cancer Effect Of Natural Productsmentioning
confidence: 99%
“…BALB/c mice were mainly used as animal models for research in vivo. Among apoptosis-inducing natural products, matrine, neferine, osthole, TR35, curcumin, acetyl-macrocalin B, JDA-202, oridonin, jaridonin, baohuoside-I, icariin, isoliquiritigenin, proanthocyanidin, quercetin, genistein, pristimerin, terrein, isoalantolactone, germacrone, natural borneol, gypenoside L, Rhizoma paridis saponins , avocado, black raspberry, Fructus forsythia , green husk, Marsdenia tenacissima , rhizome extract, Sutherlandia frutescens , Sutherlandia tomentosa , Daikenchuto, Rosa roxburghii Tratt , Fagopyrum cymosum , and Tonglian had little to no cytotoxicity in normal cells [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 53 , 54 , 55 , 56 , 57 ]. The rest of the research did not include cytotoxicity tests.…”
Section: Anti-esophageal Cancer Effect Of Natural Productsmentioning
confidence: 99%